The influence of the contemporary social background on the coinage of technical lexicons. The case of the lexicon of political economy in 19PthP century China - Pellin, Tommaso (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
During the second half of the 19PthP century, Chinese scholars created the lexicons of many scientific domains through the translation of Western works. The aim of this article is to describe the impact of the expectations of contemporary readers on the process of coinage of the language of political economy, as an instance of the influence of users of translations on the translator ’s work. Here I will present the results of a lexicological analysis of the first two Chinese translations of English politico- economic essays, which appeared respectively before and after 1895. This will be followed by an illustration of some historical elements for identifying the general profile of the potential readership. Finally, an analysis of the link between the lexicological choices of the translators and the expectations of their public will help to assess the weight of the reader ’s profile on the terminological work.